Trophic guilds of marine predators in the California Current Large Marine Ecosystem - Joseph J. Bizzarro; John C. Field; Jarrod A. Santora; K. Alexandra Curtis; Brian K. Wells (Frontiers in Marine Science, 2023)
Quantifying trophic relationships of marine species is fundamental to the construction and performance of ecosystem models, development of effective ecosystem-based fisheries management strategies, and support of trait-based approaches to ecological risk assessment. Accounting for food web dynamics in taxonomically diverse ecosystems, such as the California Current Large Marine Ecosystem (CCLME), is especially challenging because of the sheer number of trophic linkages and their inherent variability. Consequently, analyses that can inform the most appropriate means of aggregating species or other taxonomic groups into assemblages or guilds are critical to reducing system complexity for modeling and management, particularly when data are limited. To provide a methodological approach that is globally applicable in such cases, we define trophic guilds within biogeographic regions of the CCLME, compare results among these regions, and discuss ecological and management implications. Within each biogeographic region, predator guilds were clearly demarcated by foraging habitat (benthic, nearshore pelagic, offshore pelagic), scale of foraging movements, and trophic position. Furthermore, trophic guilds were distinctive for each region, with species composition and the noted ecological characteristics largely driving guild structure. Predator species that are reliant on continental slope and offshore foraging habitat, such as adult Pacific Hake, have diets that are representative of these areas and are similar throughout the CCLME. Generally, larger, more mobile predators that typically feed in deeper offshore waters, including swordfish, sea lions, and sharks clustered together in multiple bioregions along the coast; all reliant primarily on fishes and squids. Throughout bioregions, groundfishes preyed on benthic invertebrates (e.g., decapods, amphipods, polychaetes), while shelf-oriented pelagic predators, including smaller salmon, preyed on pelagic invertebrates (e.g., euphausiids, copepods, gelatinous zooplankton). A large number of forage taxa that are well represented in this study have dynamics largely dependent on oceanographic conditions at a regional scale (e.g., decapods), basin scale (e.g., copepods), or a combination of both (e.g., euphausiids, Northern Anchovy). Such distinctions indicate that spatial and temporal scales of coherence of predators and prey also must be considered in development of ecosystem models and evaluation of management strategies. Our study quantifies the spatial coherence of predator guilds integrated over decades within and across bioregions of the CCLME, providing an improved understanding of regional ecosystem functioning. The analytical approach we developed may be easily extended to address similar ecological and ecosystem based fisheries management priorities in other marine regions.